Implementasi Visi-Misi dan Gaya Kepemimpinan Kepala Daerah: Kajian terhadap Gubernur Jakarta Pramono Anung - Muna, Sana Rifatil; Saputra, Ananda Muhammad; Masriyiani F, Viana; Adityai, Restu; Suherman, Muhammad Revo Nazwa (Yayasan Riset dan Pengembangan Intelektual, 2025)
This article aims to examine the leadership style of Jakarta Governor Pramono Anung and analyze how his leadership vision and mission are implemented in public policies and governance practices. Employing a descriptive qualitative approach, the study draws on data from official government documents, media reports, public speeches, and interviews. Content analysis is used to interpret and identify patterns in the policies, statements, and programs initiated by the governor throughout his administration. The article applies several leadership theories as an analytical framework, including democratic leadership, paternalistic, charismatic, open leadership, and militaristic styles. The findings reveal that Pramono Anung predominantly adopts a democratic and open leadership approach through public dialogues and citizen engagement forums, complemented by a paternalistic style that emphasizes communication and emotional connection with constituents. His vision and mission are reflected in key programs such as digitalization of public services, the involvement of civil servants in transportation reforms, and empowerment of local communities. Overall, Pramono Anung’s leadership style demonstrates flexibility and adaptability in navigating the complexities of Jakarta as Indonesia’s capital. His openness to public criticism, symbolic leadership acts, and alignment between vision and concrete actions are strengths that support effective governance. Nevertheless, bureaucratic resistance and implementation gaps remain significant challenges that must be continuously addressed.